The Student’s Perceptions of Netflix Movies in Learning English to Improve Writing Skills on Vocational High School - Ibrahim, Ahmad; Ahmad, Zuhad; Ma’mun, Akhmad Haqiqi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study investigates how students feel about using Netflix as an additional English language learning resource to improve their writing abilities in vocational high schools. The increasing significance of technology in education makes it necessary to understand the positive effects of non-traditional platforms such as Netflix when it comes to language learning. The study employs a qualitative approach, and interviews to gather insights from vocational high school students engaged in English language learning through Netflix. This article aims to investigate students’ perceptions of the use of Netflix in the context of English language learning, and to investigate students’ How does the use of Netflix contribute in the context of English language learning, particularly in the development of writing skills. The study findings will be the knowledge which can be implemented in the future prospect as the educator, specifically when facing the related problem about The Student Perceptions of Netflix in Learning English to Improve Writing Skills on Vocational High School.